The effects of government SMS in Taiwan. (1st January 2010) - Ho, Li-Hsing; Chung, Cheng-Wei; Chen, Huan-Tun; Lee, Amy H.I.
Short message services (SMS) technology, because of its high personalisation, instantaneity and convenience, can surpass traditional methods for communication. This research was carried out using the questionnaire method, and the sampling was done by the snowball method, which ensured that the respondents did receive SMS message from the public sector. It was found that the attitude of people has a significant impact on the effects of communication, especially in terms of enhancing the positive impression of the public towards the digitalisation efforts of government departments. Among the SMS receivers, 93.5% of people who successfully received the SMS opened and read the message, while 7.3% of people forwarded it. This shows that using SMS for sending information has the effect of informing the public. However, the public sector must find ways to further encourage people to forward the information. In addition, this research found that sending policy announcements through SMS at 10am yielded the best results, while 3pm proved to be the best time to send tourism-related information. Therefore, we conclude that sending the right kind of information at the right time can contribute to raising the public's satisfaction towards government departments.